(3chcH GdeQjN aj NdGUI GdJGQjNs - (3eMeO YGQa Hf CMeO GdTGcQ Hf LQLjS GdehUdj GdWGFj GdMfajs
(3ChdgG (B:s
(3CeG HYO deG cKQ ENJdGa Ggd GdJGQjN aj GdeOI GdJj ef BOGe Ydjg GdUdGI hGdSdGe Edi Ref GdSfI GdgLQjI hbO WdH efj ef dGjSYafj GdJNda Yf CeQg Cf CHjf eG gh GdoeYJeO Ydjg s
(3BNQgG (B:s
(3dCf XGgQ GdfUhU JOd Ydi caQ CHj WGdH ade jfaYg JUOjbg, hGddg CYde s
(3GdJhKjbGJ GdeQLYjI (B:s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B4 - (3U (B349 s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG JdhjK s
(3eUOQ GbJfGA GdCUd (B:s
(3LGeYI HZOGO (B(442) s
Keywords: (3GdJGQjNs